2014
DOI: 10.7250/pee.2014.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Untransposed Power Lines

Abstract: -Keywords -current sequence of three-phase system, flat phase arrangement, mutual impedances, self impedances, untransposed power line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…To make the calculation plausible, it is necessary to unscramble all the components of the expressions (2) referring to the sections 2 and 8 of [8], where zd = 0.148 + 0.7227i; zs = 0.05 + 0.3422; zf = 0.05 + 0.2987i.…”
Section: Determination Of Unbalanced Loadmentioning
confidence: 99%
See 4 more Smart Citations
“…To make the calculation plausible, it is necessary to unscramble all the components of the expressions (2) referring to the sections 2 and 8 of [8], where zd = 0.148 + 0.7227i; zs = 0.05 + 0.3422; zf = 0.05 + 0.2987i.…”
Section: Determination Of Unbalanced Loadmentioning
confidence: 99%
“…In [8], it is shown that a power line becomes balanced if all mutual impedances are equal. If in flat arrangement of phases, the mutual inductance between two outside phases were equal to that between adjacent phases, then the power line would become balanced.…”
Section: B Phase a (With A Set Load) In The Middlementioning
confidence: 99%
See 3 more Smart Citations